2020
DOI: 10.24235/sc.educatia.v9i1.6440
|View full text |Cite
|
Sign up to set email alerts
|

Developing STEM-Based Student Worksheet to Improve Students’ Creativity and Motivation of Learning Science

Abstract: The Student worksheet based on science, technology, engineering, and mathematics (STEM) has been prepared, validated, and tested on students at SMAN 5 Banda Aceh. The worksheet guided the students to design a salt-making tool with a sunlight-gathering mirror. The worksheet was developed using the ADDIE model of the research and development (R&D) method. The subjects of the study consisted of 31 students divided into some groups consisting of 6 participants for each. The students were given problems and example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In line with the opinion of Husna et al, (2020) explaining that the implementation of STEM-based worksheets can significantly increase the learning motivation of students. The PBL model can also motivate students to achieve the desired learning outcomes.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In line with the opinion of Husna et al, (2020) explaining that the implementation of STEM-based worksheets can significantly increase the learning motivation of students. The PBL model can also motivate students to achieve the desired learning outcomes.…”
Section: Resultssupporting
confidence: 69%
“…Previous research on the use of PBL learning models combined with STEM-based worksheets was conducted by Husna et al, (2020) explaining that the use of STEM-based worksheets can significantly increase learning motivation and creativity of students. The motivation to learn and the curiosity of students must be endeavored to increase learning involvement and creativity during class.…”
Section: Resultsmentioning
confidence: 99%
“…Implementation of STEM approaches through EDP with PjBL models to improve mathematical creative thinking skills Jawad et al, (2021) in his research obtained results that with STEM learning can develop innovative thinking, improve student achievement because with STEM learning can create an atmosphere of passion that attracts students to the field, motivates to learn, creativity and innovate. Husna et al, (2020) found the highest score on the aspect of creativity is creative in solving problems. Calculated using the percentage formula and comparing the creativity assessment category table to determine what categories are obtained.…”
Section: Figure 2 Experimental Class Test Resultsmentioning
confidence: 98%
“…Maluku is one of the provinces in Indonesia IPA are means think scientific and one key main in find relationship and regularity Among a number of thing to be disclose draft about nature (Husna et al, 2020). IPA is also a right method think logical with characteristic systematic , careful and thorough as possible give utility practical in life needed everyday solving in a manner careful and thorough (Fauziah & Nurita, 2019).…”
Section: Introductionmentioning
confidence: 99%